1999
DOI: 10.1093/ee/28.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protect-It on Efficacy ofAnisopteromalus calandrae(Hymenoptera: Pteromalidae) Parasitizing Rice Weevils (Coleoptera: Curculionidae) in Wheat

Abstract: The parasitoid Anisopteromalus calandrae (Howard) was very sensitive to direct contact with Protect-It, an inert dust formulation containing 90% diatomaceous earth and 10% silica aerogel. LT 50 s at room temperature and humidity were 49 min (95% CL ϭ 48 Ð51) and 72 min (95% CL ϭ 69 Ð74) for males and females, respectively, in petri dishes containing 2.5 mg dust per square centimeter. Under the same conditions, adults of the rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae), a host of A. calandrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 20 publications
(17 reference statements)
1
11
0
2
Order By: Relevance
“…Although neither the wheat nor the corn used in this study was actually equilibrated to the desired moisture content, results from other studies using saturated salt solutions have documented consistent inverse relationship between RH and mortality of insects exposed on DEtreated grains (Perez-Mendoza et al 1999, Arthur 2002. Reductions in efÞcacy of DE on corn compared with wheat have been made by Subramanyam et al (1994) and by Subramanyam and Roesli (2000) in reference to unpublished data, and they state that the differences in lipid and starch content of corn may be responsible for the loss of activity.…”
Section: Discussionmentioning
confidence: 74%
“…Although neither the wheat nor the corn used in this study was actually equilibrated to the desired moisture content, results from other studies using saturated salt solutions have documented consistent inverse relationship between RH and mortality of insects exposed on DEtreated grains (Perez-Mendoza et al 1999, Arthur 2002. Reductions in efÞcacy of DE on corn compared with wheat have been made by Subramanyam et al (1994) and by Subramanyam and Roesli (2000) in reference to unpublished data, and they state that the differences in lipid and starch content of corn may be responsible for the loss of activity.…”
Section: Discussionmentioning
confidence: 74%
“…For example, diatomaceous earth is more toxic to A. calandrae than to S. oryzae (Perez-Mendoza et al 1999). By direct contact, diatomaceous earth takes Ͼ1 h to kill 50% of A. calandrae, but it takes 24 h to kill 50% of its host, S. oryzae (Perez-Mendoza et al 1999). In contrast, our studies demonstrated that protein-rich pea ßour and parasitoids were compatible for reducing populations of S. oryzae and C. ferrugineus.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike diatomaceous earth (Korunic et al 1998, Fields andKorunic 2000), pea protein ßour did not reduce bulk density. Also, most grain protectants harm parasitoids (Perez-Mendoza et al 1999). Protein-enriched pea ßour is not toxic to Anisopteromalus calandrae (Howard), an ectoparasitoid of several stored-product insects, and Cephalonomia waterstoni (Gahan), an ectoparasitoid of C. ferrugineus (Hou et al 2002).…”
Section: Discussionmentioning
confidence: 99%